Commentary: COVID-19 healthcare barriers around vaccine uptake among migrant workers within the Canadian Prairies - Anthony Huynh; Souradet Shaw; Lisa Lazarus; Diwa Marcelino; Robert Lorway (Taylor & Francis Group, 2024)
This commentary explores the vulnerabilities faced by temporary foreign workers (TFWs) in Manitoba, Canada within the context of the COVID-19 pandemic. TFWs often endure substandard working conditions and lack access to essential healthcare services due to their status as non-citizens. The COVID-19 pandemic has further exacerbated their precarious situation, with TFWs experiencing disproportionately high rates of infection. Conducted in partnership between Migrante Manitoba and the University of Manitoba's Institute for Global Public Health, our research aimed to examine the healthcare barriers around vaccine uptake among TFWs in Manitoba by locating it within the wider structural context of inequality. We highlight the need for a comprehensive understanding of the unique healthcare needs and barriers faced by TFWs.